Carbon Storage of Shelterbelts in Yunnan Province and Countermeasures for Increasing Carbon Sinks - Zhang Kaidi; Su Jianlan (E3S Web of Conferences, 2023)
Based on the data of seven national forest inventory and the fourth second-class forest inventory in Yunnan Province, the biomass expansion factor method was used to calculate the carbon storage dynamics of shelterbelts in Yunnan Province. The results show that: 1) the carbon storage of shelterbelts in Yunnan Province increased from 8868.03×104 tons in 1988 to 37635.01×104 tons in 2018, with an average annual growth of 821.91×104 tons. The contribution rate of shelterbelts carbon storage to the total forest carbon storage in Yunnan Province increased from 17.59% to 41.63%, and the total average carbon density of shelterbelts showed an upward trend in fluctuation. 2) the contribution rate of carbon storage of middle-aged forest (20.20%-27.44%) was the largest, the mature forest and overmature forest was the second and third, and the contribution rate of carbon storage of young forest was the lowest. The total average carbon density of shelterbelts increased with the age classes. 3) The natural shelterbelts had been the main contributor to the carbon storage in Yunnan, and its contribution rate (between 95.80% and 99.53%) decreases gradually, while the carbon density of natural shelterbelts increases with the increase of age. Compared with natural shelterbelts, the carbon storage and density of artificial shelterbelts were at a lower level, and the total average carbon density of artificial shelterbelts is on the rise. The carbon density of artificial shelterbelts of different ages is mature forest > near mature forest > over mature forest > middle aged forest > young forest. 4) Diqing Prefecture was the main contributor of carbon storage of shelterbelts in Yunnan Province (the contribution rate is 17.65%), and the carbon storage of shelterbelts in northwest Yunnan accounts for 44.19% of the total carbon storage of shelterbelts in Yunnan Province. Yunnan province should pay attention to the maturity of middle-aged and young shelterbelts, strengthen the management of artificial shelterbelts to enhance the carbon storage capacity of Yunnan shelterbelts.